Substrate reduction therapy for Krabbe disease and metachromatic leukodystrophy using a novel ceramide galactosyltransferase inhibitor - Michael C. Babcock (Nature Portfolio, 2021)
Abstract Krabbe disease (KD) and metachromatic leukodystrophy (MLD) are caused by accumulation of the glycolipids galactosylceramide (GalCer) and sulfatide and their toxic metabolites psychosine and lysosulfatide, respectively. We discovered a potent and selective small molecule inhibitor (S202) of ceramide galactosyltransferase (CGT), the key enzyme for GalCer biosynthesis, and characterized its use as substrate reduction therapy (SRT). Treating a KD mouse model with S202 dose-dependently reduced GalCer and psychosine in the central (CNS) and peripheral (PNS) nervous systems and significantly increased lifespan. Similarly, treating an MLD mouse model decreased sulfatides and lysosulfatide levels. Interestingly, lower doses of S202 partially inhibited CGT and selectively reduced synthesis of non-hydroxylated forms of GalCer and sulfatide, which appear to be the primary source of psychosine and lysosulfatide. Higher doses of S202 more completely inhibited CGT and reduced the levels of both non-hydroxylated and hydroxylated forms of GalCer and sulfatide. Despite the significant benefits observed in murine models of KD and MLD, chronic CGT inhibition negatively impacted both the CNS and PNS of wild-type mice. Therefore, further studies are necessary to elucidate the full therapeutic potential of CGT inhibition.